Mass conservatism : the Conservatives and the public since the 1880s - Ball, Stuart, 1956-; Holliday, Ian (British politics and society., 2002)
"The essays in this volume explore the relationship between the Conservative Party and the mass of the British people from the 1880s to the Thatcher and Major era. Several focus upon the party's sources of support and the ways in which it has sought to broaden these through shifts in policies, presentation and organisation."--Jacket